1997
DOI: 10.1021/jp9716086
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Active Species in Alkali-Ion-Modified Silica-Supported Vanadium Oxide

Abstract: Silica-supported vanadium oxide (V2O5/SiO2) and alkali-ion (Na+, K+, or Rb+)-modified V2O5/SiO2 samples have been characterized by diffuse reflectance UV−vis spectroscopy, Raman spectroscopy, X-ray absorption spectroscopy (XANES and EXAFS), and XPS. The structure of vanadium species in V2O5/SiO2 has been confirmed to be of a (VO)O3 tetrahedron. The addition of alkali ions to V2O5/SiO2 has caused neither the change of the coordination number of vanadium ions nor the formation of alkali vanadates on the silica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 26 publications
6
38
0
Order By: Relevance
“…Evidence is based on the observation of transient loss of V-O-H absorption upon photoreaction and the fact that hydroxylated vanadyl centers absorb in the blue spectral region while isolated vanadyl groups in a completely dehydrated state do not. On the other hand, it has been reported that vanadia centers in the hydrated state are not active in photo-oxidation reactions [3,24]. This is confirmed in the present study, since accumulation of water on the catalyst leads to a significantly lower activity in the photo-oxidation of cyclohexene.…”
Section: 2supporting
confidence: 87%
“…Evidence is based on the observation of transient loss of V-O-H absorption upon photoreaction and the fact that hydroxylated vanadyl centers absorb in the blue spectral region while isolated vanadyl groups in a completely dehydrated state do not. On the other hand, it has been reported that vanadia centers in the hydrated state are not active in photo-oxidation reactions [3,24]. This is confirmed in the present study, since accumulation of water on the catalyst leads to a significantly lower activity in the photo-oxidation of cyclohexene.…”
Section: 2supporting
confidence: 87%
“…[11][12][13][14][15] This classical model is characterized by a vibration at ∼1020-1040 cm -1 , as measured with Raman spectroscopy. 16 The exact frequency depends on the support material.…”
Section: Introductionmentioning
confidence: 92%
“…In general, the VO 4 monomeric species in dehydrated supported vanadium oxide catalysts has been envisaged as a distorted tetrahedral structure with one Vd O bond and three VsO b sM support bonds. [17][18][19][20][21] Although this classical VO 4 model is most widely accepted in literature, recent studies demonstrated, with results obtained from EXAFS at 77 K in combination with structural models, that for supported vanadium oxide species a single VsO b sM support bond can be formed on alumina, silica, niobia, and zirconia supports. [22][23][24] The structure of the interface between the support oxide material and the VO 4 cluster has also been recently determined.…”
Section: Introductionmentioning
confidence: 99%